New Constellations : Movie Stars of the 1960s - Wojcik, Pamela Robertson, 1964- (Book collections on Project MUSE., 2012)
New Constellations: Movie Stars of the 1960s tells the story of the final glory days of the studio system and changing conceptions of stardom, considering such Hollywood icons as Elizabeth Taylor and Paul Newman alongside such hallmarks of youth culture as Mia Farrow and Dustin Hoffman. Others, like Sidney Poitier and Peter Sellers, took advantage of the developing independent and international film markets to craft truly groundbreaking screen personae. And some were simply "famous for being famous," with celebrities like Zsa Zsa Gabor and Edie Sedgwick paving the way for today'